Basic Spanish for Malaysian students: learning difficulties - Mansor, Nor Shahila; Abdul Aziz, Norazah; Olmedo, Beatriz Valverde; Mohd Nor, Mariyati (Faculty of Education, Universiti Teknologi MARA Selangor, 2022)
The present study identifies the difficulties in learning Spanish as a foreign language among Malaysian students. The data presented in this study was collected through; 1) interviews with ten (10) students between 20 to 23 years old enrolled in the Basic Spanish Language course at the Universiti Putra Malaysia and 2) in-class activities and assessments answered by these students. The data collected were analysed using a qualitative-descriptive approach. The results show that Malaysian students face a series of difficulties that hinder them from acquiring adequate competence in Spanish, namely the lack of lexis, pronunciation ability and grammar, particularly verbal conjugation. The findings of this study have implications for the teaching and learning of Spanish as a foreign language in Malaysia, whereby it can be used as guidance for Spanish language educators to design suitable teaching and learning activities to facilitate Malaysian students' understanding and mastery of Spanish as a foreign language.